ANALYSIS OF TEACHER BARRIERS IN THE IMPLEMENTATION OF CURRICULUM MERDEKA IN SECONDARY SCHOOLS - Saputra, Andra; Gistituati, Nurhizrah; Ambiyar, Ambiyar; Bentri, Alwen; Aziz, Ishak; Hidayati, Abna (Dharmas Education Journal (DE_Journal), 2024)
This research aims to analyze the obstacle factors faced by teachers in implementing the Independent Curriculum in Middle Schools. The obstacle factors analyzed were reviewed from several aspects adapted to the literature, namely; Aspects of teacher understanding of the philosophy and objectives of the Independent Curriculum, aspects of teacher pedagogical skills, aspects of teacher technology readiness, aspects of collaboration between teachers, aspects of administrative support, aspects of parent participation, aspects of resource availability. The research uses a qualitative survey approach with a case study design. This research involves selected teachers as participants, who provide in-depth insight through in-depth interviews, classroom observations, and document analysis. The research results show that aspects of teacher understanding of the philosophy and objectives of the Independent Curriculum with a percentage of 83.60%, aspects of teacher pedagogical skills with a percentage of 85.20%, aspects of teacher technology readiness with a percentage of 79.33%, aspects of collaboration between teachers with a percentage of 84.27 %, administrative support aspect with a percentage of 85.73%, parental participation aspect with a percentage of 86.27%, resource availability aspect with a percentage of 85.33%. This research provides a foundation for changing educational policies and approaches to address these barriers. Conclusions emphasize the need for better training, consistent administrative support, and strengthened collaboration between teachers, school officials, and parents to ensure successful implementation of the Merdeka Curriculum in Secondary Schools.